A escuta do mundo da vida na constituição de uma sociedade emancipatória - Brunetti, Renata (2007)
The objective of the research that originated this text was, by means of the analysis of the interviews with a few Ashoka fellows social figure, try to identify spaces in our society, in which actions that promote emancipation are possible. Trying to locate models, recipes, pre-defined and replicable solutions; however, the reading and listening during the works carried us in another direction. Some forms of defining a name for the social figure were questioned, since they don t spontaneously fit as entrepreneurs, nor as the well known militant. Social poets and polyglots were names used in this work to enhance their qualities in social listening and mediation. The interview analyses showed they strongly value local knowledge, are multifocal have multiple interests, are incapturable. Differently from the old paradigm, instead of defining forms of producing the world, they go out there the world, Habermas life-world listening and translating it, and mediating it with the systemic world . The main theoretical inspiration belongs to the philosopher J. Habermas. We reflected some of his recent theoretical concerns, not avoiding however, referring to other authors and propositions. High interests were placed in providing sense and meaning to our interviewees. Thus in this work, theory is at the service of an empirical world. The comprehension of the experience performed with our interviewees as well as that of the interviewees with their communities was the key element, that as such, selected the theory. Lastly, the work suggests that these social figures, with their actions, seem to rehearse changes in the political culture with the strengthening of civil society, as well as a change in knowledge paradigm. The rehearsal a political culture that may results, first and foremost, in facing our conscious individual and social responsibilities